2013
DOI: 10.1111/jopy.12028
|View full text |Cite
|
Sign up to set email alerts
|

A Basic Bivariate Structure of Personality Attributes Evident Across Nine Languages

Abstract: Here, two studies seek to characterize a parsimonious common‐denominator personality structure with optimal cross‐cultural replicability. Personality differences are observed in all human populations and cultures, but lexicons for personality attributes contain so many distinctions that parsimony is lacking. Models stipulating the most important attributes have been formulated by experts or by empirical studies drawing on experience in a very limited range of cultures. Factor analyses of personality lexicons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
189
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(207 citation statements)
references
References 55 publications
9
189
1
Order By: Relevance
“…While the majority of this work has been conducted with North American and Western European samples, there is some evidence that is consistent with the possibility that the A and C dimensions are culturally universal (Abele et al, 2008c; Ybarra et al, 2008; Saucier et al, 2014). …”
Section: The Agency—communion Frameworksupporting
confidence: 54%
See 1 more Smart Citation
“…While the majority of this work has been conducted with North American and Western European samples, there is some evidence that is consistent with the possibility that the A and C dimensions are culturally universal (Abele et al, 2008c; Ybarra et al, 2008; Saucier et al, 2014). …”
Section: The Agency—communion Frameworksupporting
confidence: 54%
“…Although cultures differ in social orientation, preliminary evidence suggests that the fundamental content dimensions of A and C do emerge across cultures (Abele et al, 2008b; Ybarra et al, 2008; Bi et al, 2013; Abele, 2014; Saucier et al, 2014). To date there is, however, no evidence that the proposed distinction of AA, AC, CW, and CM can be reliably established across cultures.…”
Section: Agency and Communion Across Culturesmentioning
confidence: 99%
“…Notably, studies of personality in humans and chimpanzees ( Pan troglodytes ), who shared a common ancestor approximately six million years age (Glazko & Nei, 2003), have demonstrated that this period of time is long enough for differences in how personality traits are organized into dimensions to emerge (King & Figueredo, 1997). Human personality structure is largely seen to consist of five broad, universal dimensions labeled Neuroticism, Extraversion, Openness to Experience, Agreeableness, and Conscientiousness (Digman, 1990; McCrae, Terracciano, & 78 Members of the Personality Profiles of Cultures Project, 2005; Schmitt et al, 2007), though this view is not shared by all researchers (see, e.g., Gurven, von Rueden, Massenkoff, Kaplan, & Lero Vie, 2013; Saucier et al, 2013). Chimpanzee personality, on the other hand, is organized around five similar dimensions plus a sixth dimension, Dominance, that reflects a combination of assertiveness, low fear, competence, and intelligence (King & Figueredo, 1997).…”
mentioning
confidence: 99%
“…Conscientiousness), and dynamism (cf. Extraversion) have been replicated [17, 18, 19]. Such contrary findings continue to drive the scrutiny and testing of personality measurement [20].…”
Section: Introductionmentioning
confidence: 99%